Az illír mozgalom magyar kötődései – horvát szemmel II. - Lukács, István; Kálecz-Simon, Orsolya (Slavia Centralis, 2020)
The article provides a historical overview of the Croatian scientific interpretation of Hungarian contacts and spiritual-political patterns in the development of the Croatian Illyrian movement. The first part of the study focuses on basic modern theoretical views on the reconstruction of historical narratives and Croatian scientific achievements in the research of the pre-Illyrian period. The second part presents how the development of the Hungarian national consciousness influenced the development of the Croatian national consciousness, why the common Hungarian National Assembly became the medium of transmission of new ideas and how the newly established Hungarian institutions, infrastructural and economic initiatives, the struggle for the Hungarian language, the Hungarian press and political ideas formed the Croatian national modernization.
Keywords: Illyrian movement; Croatian-Hungarian spiritual contacts; development of Hungarian and Croatian national consciousness